ANALISIS KOEFISIEN LIMPASAN PERMUKAAN KOTA MAKASSAR DENGAN METODE COOK - Sudirman Nganro; Slamet Trisutomo; Roland Alexander Barkey; Mukti Ali (Diponegoro University, 2019)
Rain falling on the Watershed will turn into a stream in the river, this is because the rainwater is not entirely infiltrated into the soil, the unabsorbed water is called surface runoff. Factors affecting runoff are meteorological elements and drainage elements. This study aims to calculate the surface runoff coefficient using land cover maps 2017 and 2050, slope and soil type as parameters. Cook method divides the watershed characteristics into 4 sections as parameters to calculate the runoff coefficient of topography, soil type, vegetation cover and surface deposit. Each parameter is weighted based on its characteristics to calculate the coefficient of surface runoff symbolized by the letter C. The analysis results show that in the year 2017 obtained the value of C = 0.4734 and for the year 2050 C = 0.4785. There's a difference of 0.0051 coefficient of runoff value between land use map and land cover in 2017 and 2050. The results of this study will be used to calculate the flood discharge design in the object of research in Makassar City.